2014
DOI: 10.1111/gfl.12092
|View full text |Cite
|
Sign up to set email alerts
|

Source and character of syntaxial hydrothermal calcite veins in Paleoproterozoic crystalline rocks revealed by fine‐scale investigations

Abstract: Calcite veins in Paleoproterozoic granitoids on the Baltic Shield are the focus of this study. These veins are distinguished by their monomineralic character, unusual thickness and closeness to Neoproterozoic dolerite dykes and therefore have drawn attention. The aim of this study was to define the source of these veins and to unravel their isotopic and chemical nature by carrying out fine-scale studies. Seven calcite veins covering a depth interval of 50-420 m below the ground surface and composed of breccias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 73 publications
(211 reference statements)
1
8
0
Order By: Relevance
“…wt% CaCl 2 corresponding to brine, and homogenization temperatures in the range of 77-218 • C [33], which at least for the salinities correspond to fluid inclusions in similar fracture coating calcite in Oskarshamn and Forsmark in Sweden, from southern Finland, and to Caledonian mineralizations [19,53,[69][70][71]. The δ 18 O values of calcite and quartz [33,72] at Lockne are also in line with compositions of the fracture-filling calcite reported from other parts of the Fennoscandian shield [19,53,[69][70][71]73]. Most of the fluid inclusion homogenization temperatures in the previous study [33] were in the 100-180 • C range, which is generally too high for microbial activity.…”
Section: New Age Constraints For the Fracture Assemblage In The Impacsupporting
confidence: 76%
“…wt% CaCl 2 corresponding to brine, and homogenization temperatures in the range of 77-218 • C [33], which at least for the salinities correspond to fluid inclusions in similar fracture coating calcite in Oskarshamn and Forsmark in Sweden, from southern Finland, and to Caledonian mineralizations [19,53,[69][70][71]. The δ 18 O values of calcite and quartz [33,72] at Lockne are also in line with compositions of the fracture-filling calcite reported from other parts of the Fennoscandian shield [19,53,[69][70][71]73]. Most of the fluid inclusion homogenization temperatures in the previous study [33] were in the 100-180 • C range, which is generally too high for microbial activity.…”
Section: New Age Constraints For the Fracture Assemblage In The Impacsupporting
confidence: 76%
“…Although optical-CL studies of opening-mode fractures in sedimentary carbonate rocks yield important insights (e.g., Trave et al, 1998;Hood et al, 2003;Holland and Urai, 2010;Vandergiste et al, 2013;Lavenu et al, 2013;Kotta, 2014), compared to SEM-CL, the low spatial resolution, magnification, and sensitivity of optical-CL means that only broad textural distinctions are possible rather than the fine resolution needed to document crack-seal gap deposits that track increments of fracture widening that may be only a few to tens of microns wide. Optical-CL studies of carbonate minerals reveal coarse zoning patterns between red-, blue-, and bright-and dull-luminescent areas from walls to inner parts of fractures in many deformed sedimentary (Trave et al, 1998;Hood et al, 2003;Berryman, 2013;Lavenu et al, 2013) and crystalline rocks (Blyth et al, 2004;Maskenskaya et al, 2014 Figure 2 are the first example of this type of structure in calcite fracture cement. Simplified diagrams of the basic textural types identified in this study are shown in Figure 9.…”
Section: Discussionmentioning
confidence: 98%
“…Fracture mineralisation in the crystalline basement of southern Sweden has been investigated extensively to evaluate potential geological nuclear waste repository facilities. Several studies have shown that most trace element concentrations vary over an order of magnitude within calcite samples (at the thin section scale), and up to several orders of magnitude across individual fractures (Drake et al, 2012(Drake et al, , 2014Maskenskaya et al, 2014;Milodowski et al, 2018). These authors suggest that (1) trace element chemistry does not trace the source rock of the metals; (2) the co-variation in most trace elements implies changing metal / Ca ratios in the fracture waters; and (3) in situ factors affect trace element incorporation, such as microbial activity, metal speciation, crystal habit, water type, and coprecipitation of other phases such as barite and pyrite.…”
Section: U and Pb Contents In Carbonatementioning
confidence: 99%